A Microfluidic Human Model of Blood–Brain Barrier Employing Primary Human Astrocytes. Issue 7 (8th May 2019) - Lauranzano, Eliana; Campo, Elena; Rasile, Marco; Molteni, Raffaella; Pizzocri, Marco; Passoni, Lorena; Bello, Lorenzo; Pozzi, Davide; Pardi, Ruggero; Matteoli, Michela; Ruiz‐Moreno, Ana
Abstract: The neurovascular unit (NVU) is the most important biological barrier between vascular districts and central nervous system (CNS) parenchyma, which maintains brain homeostasis, protects the CNS from pathogens penetration, and mediates neuroimmune communication. T lymphocytes migration across the blood–brain barrier is heavily affected in different brain diseases, representing a major target for novel drug development. In vitro models of NVU could represent a primary tool to investigate the molecular events occurring at this interface. To move toward the establishment of personalized therapies, a patient‐related NVU‐model is set, incorporating human primary astrocytes integrated into a microfluidic platform. The model is morphologically and functionally characterized, proving to be an advantageous tool to investigate human T lymphocytes transmigration and thus the efficacy of potential novel drugs affecting this process. Abstract : An in vitro model of the neurovascular unit (NVU) is set using human brain endothelial cells and primary human astrocytes growing at the two sides of a matrix‐coated permeable membrane. The human NVU model, integrated into a microfluidic platform, is exploited to investigate human T lymphocytes recruitment and transmigration with real‐time high‐resolution 4D imaging.